Palladium-Catalyzed C7–H (Hetero)arylation of Pyrazolo[1,5-a]pyrazines with Heteroarenes and Aryl Iodides with the Assistance of Silver Salts - Nguyen, Thanh V. Q.; Levoin, Armand; Poli, Lorenzo (Synthesis, 2023)
Pyrazolo[1,5-a]pyrazines coupled with heteroarenes and aryl iodides selectively at the C7 position to afford a broad library of bi(hetero)aryl structures under ligand-free palladium-catalyzed conditions. The key to the success of the reaction is the use of silver salts as the oxidant or the base, allowing the regioselective C–H bond functionalization to occur under relatively mild conditions.
Keywords: C–H bond functionalization; fused-ring systems; heteroarenes; homogeneous catalysis; synthetic methods